A survey on some biochemical and pharmacological activities of venom from two Colombian colubrid snakes, Erythrolamprus bizona (Double-banded coral snake mimic) and Pseudoboa neuwiedii (Neuwied's false boa). (1st June 2017) - Torres-Bonilla, Kristian A.; Floriano, Rafael S.; Schezaro-Ramos, Raphael; Rodrigues-Simioni, Léa; da Cruz-Höfling, Maria Alice
Abstract: Colombian colubrid snake venoms have been poorly studied. They represent a great resource of biological, ecological, toxinological and pharmacological research. We assessed some enzymatic properties and neuromuscular effects of Erythrolamprus bizona and Pseudoboa neuwiedii venoms from Colombia. Proteolytic, amidolytic and phospholipase A2 (PLA2 ) activities were analyzed using colorimetric assays and the neuromuscular activity was analyzed in chick biventer cervicis (BC) preparations. The venom of both species showed very low PLA2 and amidolytic activities; however, both exhibited high proteolytic activity, which in E. bizona venom surpassed that of P. neuwiedii venom. E. bizona and P. neuwiedii venoms provoked partial neuromuscular blockade, which was more prominent in P. neuwiedii venom. E. bizona venom (30 μg/ml) induced a significant potentiation of the contracture response to exogenous ACh (110 μM), which was not accompanied by twitch height alteration, whereas the highest venom concentration (100 μg/ml) inhibited contracture responses to both ACh and KCl (40 mM). In contrast, P. neuwiedii venom (30 and 100 μg/ml) caused significant reduction in the contracture responses to exogenous ACh and KCl. The morphological analyses showed high myotoxic effects in the muscle fibers of BC incubated with either venoms; however, they are more prominent in the P. neuwiedii venom. Our results suggest that the myotoxicity of the venom of the two Colombian species can be ascribed to their high proteolytic activity. An interesting data was the potentiation of the ACh-induced contracture, but not the twitch height, caused by E. bizona venom, at a concentration that is harmless to muscle fibers integrity. This phenomenon remains to be further elucidated, and suggest that a possible involvement of post-synaptic receptors cannot be discarded. This work is a contribution to expand the knowledge on colubrid venoms; it allows envisaging that the two venoms offer the potential to go further in the identification of their components and biological targets. Highlights: E. bizona and P. neuwiedii venom induced partial neuromuscular blockade in chick biventer cervicis preparations. E. bizona (Double-banded coral snake mimic) venom (30 μg/ml) potentiated the ACh-induced contracture without changing the twitch tension. P. neuwiedii (Neuwied's false boa) venom myotoxicity is higher than E. bizona venom and is likely due to proteolytic activity. The venom of both species showed low phospholipase A2 activity. The neuromuscular blockade observed is likely induced by muscle damage in consequence of their high proteolytic activity.